1990
DOI: 10.1136/bmj.301.6761.1134
|View full text |Cite
|
Sign up to set email alerts
|

Measuring readmission rates.

Abstract: Milne deal with the issue of using readmission rates as an outcome indicatorfor hospital care. Thefirst paper assesses thefeasibility ofmeasuring readmission ratesfrom routinely collected Korner data in a study of three districts in North East Thames region and the second, based on a study in one district, whether readmissions may be judged as avoidable or unavoidable. The third article examines the validity of using readmission rates as an outcome indicator, and the authors conclude that such an approach is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0
5

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 6 publications
7
45
0
5
Order By: Relevance
“…For each specialty, the distribution of time between successive admissions exhibited a lognormal or exponential shape with approximately 32% of admissions occurring within 28 days after discharge. A similar pattern was found by Chambers et al [2], where time between successive admissions was showed to have an early peak (0-6 days), and then gradually levelled off after 28 days. However in both cases, the justification for the choice of 28 days relied solely on visual inspection of the histograms, therefore, it could result in an inaccurate estimation.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…For each specialty, the distribution of time between successive admissions exhibited a lognormal or exponential shape with approximately 32% of admissions occurring within 28 days after discharge. A similar pattern was found by Chambers et al [2], where time between successive admissions was showed to have an early peak (0-6 days), and then gradually levelled off after 28 days. However in both cases, the justification for the choice of 28 days relied solely on visual inspection of the histograms, therefore, it could result in an inaccurate estimation.…”
Section: Introductionsupporting
confidence: 63%
“…This approach, which takes a process point of view, can be shown [8] to be equivalent to the patient group argument presented in Section 2.1. In particular, the pdf of the mixture distribution (1) can be expressed by in terms of rates as p = q 10 − q 20 q 10 + q 12 − q 20 (2) and f 1 (x) and f 2 (x) are exponential density functions with parameters λ 1 = q 10 + q 12 and λ 2 = q 20 respectively. Therefore, the optimal cut-off time x * is computed by…”
Section: Coxian Phase-type Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Otros factores son dependientes del tipo de enfermedad (8,21,24,25), siendo en general la tasa de reingreso más baja cuando la enfermedad es de tratamiento quirúrgico, de la gravedad del proceso clínico (34) y del seguimiento del enfermo (35). La tasa de reingreso es más alta en ancianos, particularmente en el anciano frágil (32) y la insuficiencia cardiaca uno de los problemas médicos con índi-ce de reingreso más alto (35,37).…”
Section: Discussionunclassified
“…Paradójicamente a lo que parece esperable, el efecto de la estancia media en ingresos previos, o no tiene influencia (24), o a mayor estancia mayor índice de reingreso (8).…”
Section: Discussionunclassified